Effect of biochar and biochar particle size on plant-available water of sand, silt loam, and clay soil - Zhang, Jun; Amonette, James E.; Flury, Markus (Soil & tillage research, 2021)
•Biochar amendment increased gravimetric plant-available water in all soils.•No effects of biochar on volumetric plant-available water were observed in silt loam and clay.•Decreasing particle size of biochar had no effect on volumetric plant-available water.•Decreasing particle size of biochar increased gravimetric plant-available water in silt loam and clay. Biochar is being used as a soil amendment to improve soil hydraulic properties. It has been reported that biochar increases plant-available water, particularly in coarse-textured soils; however, effects on fine-textured soils are less pronounced. Here, we quantified the effects of biochar particle size on plant-available water in sand, silt loam, and clay soils. We amended these soils with a hydrophilic biochar, and packed soil-biochar mixtures into columns of 5.35-cm diameter and 3.0-cm height. Biochar was produced by gasification of woody forest residues. We applied the biochar at two different rates (0.5% and 2% by weight of C) and with four different biochar particle-size fractions (<4.75, <2.0, <1.0 and <0.5 mm). Our results show that biochar amendments increased the plant-available water (when expressed gravimetrically) of all three soils, particularly at the highest biochar application rate. Although the absolute increase in plant-available water was largest for the silt loam soil, the relative increase of plant-available water was greater for the sand than for the silt loam and clay. When expressed in volumetric terms, however, the effects on water retention were less pronounced: the sand showed a small increase in plant-available water with biochar amendment, and no change was observed with the silt loam and clay. Particle size of biochar had little effect on plant-available water (when expressed in gravimetric terms) in the three soils, but silt loam and clay showed increased plant-available water (when expressed in volumetric terms) with decreasing biochar particle size, while no effect was observed for the sand. While our findings corroborate many of the previously reported effects of biochar on soil-water retention, we show that the effects and their magnitude depend on whether the results are reported in terms of gravimetric or volumetric water contents. Because bulk density tends to decrease with increasing biochar application, so will the volumetric water content, and thus the magnitude of the effect on plant-available water will be smaller when expressed in volumetric water content.